Long‐Term Effects of the Family Check‐Up in Early Adolescence on Risk of Suicide in Early Adulthood. (April 2016) - Connell, Arin M.; McKillop, Hannah N.; Dishion, Thomas J.
Abstract : The impact of the Family Check‐Up (FCU), a school‐based prevention program, as delivered in public secondary schools on suicide risk across adolescence, was examined. Students were randomly assigned to a family‐centered intervention ( N = 998) in the sixth grade and offered a multilevel intervention that included (1) a universal classroom‐based intervention, (2) the FCU (Dishion, Stormshak, & Kavanagh, 2011), and (3) family management treatment. Engagement with the FCU predicted significant reductions in suicide risk across adolescence and early adulthood.